Eksplorasi Pengalaman Mengajar Mahasiswa Calon Guru melalui Pendekatan Photovoice: Studi Fenomonologis di Sekolah Dasar Indonesia - Rismawati, Neneng; Samsu, Samsu; Rahman, Abdul (Diniyah: Jurnal Pendidikan Dasar, 2024)
This study aims to explore the emotional experiences of pre-service teachers during their Field Teaching Practice (PLP II) at SD Negeri 92 Kendari using the photovoice approach. Employing a qualitative method with a phenomenological design, data were collected through photovoice submissions and semi-structured interviews. The analysis followed three stages of coding: open coding, focused coding, and identification of critical incidents. The findings reveal that participants experienced a range of emotional states throughout the teaching practicum, including fear, anxiety, self-confidence concerns, as well as feelings of happiness, gratitude, and critical reflection. The photovoice technique proved effective in capturing and expressing the participants’ teaching experiences both visually and narratively. However, the study also faced limitations related to time constraints and data collection. This research contributes to the development of reflective methodologies in teacher education and offers insights into the emotional dynamics of novice teaching experiences.Keywords: Photovoice, teaching experience, pre-service teachers, emotional reflection, elementary education